2020
DOI: 10.3389/fvets.2020.00565
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making of Swiss Farmers and the Role of the Veterinarian in Reducing Antimicrobial Use on Dairy Farms

Abstract: The reduction of antimicrobials on dairy farms is a topical issue and confronts both veterinarians and farmers with major challenges. The aim of this study was to investigate dairy farmers' motivation to reduce antimicrobial use on their farms. Factors influencing dairy farmers' decision-making regarding dairy cow health were identified and the role of the veterinarian in these processes was characterized. A customized structured questionnaire was sent to all participants (n = 59) of an ongoing antimicrobial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Studies from Europe and North America have reported that veterinary advice is the most influential factor for AMU decision by dairy farmers ( 25 , 32 ). However, in this study, many participants reported consulting with the veterinarian only in cases of recurrent, severe, or uncommon disease or after trying different therapeutic options, indicating that the role of the veterinarian in deciding whether to administer antimicrobial treatments to cattle may be infrequent and consequently less influential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Europe and North America have reported that veterinary advice is the most influential factor for AMU decision by dairy farmers ( 25 , 32 ). However, in this study, many participants reported consulting with the veterinarian only in cases of recurrent, severe, or uncommon disease or after trying different therapeutic options, indicating that the role of the veterinarian in deciding whether to administer antimicrobial treatments to cattle may be infrequent and consequently less influential.…”
Section: Discussionmentioning
confidence: 99%
“…New technologies such as milking robots and wearable sensors, and digital sources of information such as social media, websites, and mobile apps are influential in farmers' decision-making process. Although the new communications technologies could offer a channel for valid information regarding animal health and AMU, the risk of misinformation on social media and other informal websites is high ( 32 ). Therefore, veterinarians and other advisors need to promote the use of evidence-based information among farmers, including online sources to minimize misinformation risks.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments lead to the fact that the TI, in its entirety, could then not be reduced, although the implementation level according to the protocol was higher. This possible explanation shows once again the importance of the veterinarian as a farm consultant in monitoring and reviewing udder health, to name but one example ( 65 ). If drugs are used for these treatments without consulting the veterinarian, although this was strictly not advised in the strategies, farmers may lack the know-how about which bacteria should be treated at all and at which point in time the therapy is most successful.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that if strategies with lower effect have been chosen, the reduction of AMU also is limited. On the other hand, we know from a previous questionnaire study in the autumn of 2018 that in many cases these farmers did not choose prevention strategies in their problematic area but rather according to their interest in gaining new knowledge ( 65 ). A possible explanation for this phenomenon is that the expected financial benefit is more motivating, or perhaps that they were perturbed by the effort required to solve a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Swiss dairy farms are typically smaller than the farms from previous reports on the feeding of WMA to calves, with an average herd size of 22 adult cows in 2018 (Gerber et al, 2020). Moreover, fattening veal calves on site, rather than selling them, is common on Swiss dairy farms (Lava et al, 2016).…”
Section: Introductionmentioning
confidence: 99%